2017
DOI: 10.1080/13102818.2017.1356689
|View full text |Cite
|
Sign up to set email alerts
|

Application of response surface methodology to optimize the production of antimicrobial metabolites by Micromonospora Y15

Abstract: The fermentation medium of Micromonospora Y15 was optimized to enhance the production of antimicrobial metabolites with the antimicrobial activity tested against Listeria monocytogenes. First, the optimal medium components (carbon source, nitrogen source and inorganic salt) were determined by the single factor experiment. Second, the Plackett-Burman experiment was used to screen significant factors. Third, the steepest ascent experiment was undertaken to figure out the optimal region of the significant factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…In addition, RSM has been used to optimize antimicrobial metabolite production by up to 3.86-fold, in Micromonospora sp. Y15 a sea mud isolate from the South China Sea [ 149 ]. With respect to marine fungi, RSM has also been employed to optimize culture conditions for the production of penicilazaphilone C, a new antineoplastic and azaphilone from the marine-derived fungus Penicillium sclerotiorum M-22 [ 150 ].…”
Section: High Throughput Methods To Streamline Cultivation Based Bmentioning
confidence: 99%
“…In addition, RSM has been used to optimize antimicrobial metabolite production by up to 3.86-fold, in Micromonospora sp. Y15 a sea mud isolate from the South China Sea [ 149 ]. With respect to marine fungi, RSM has also been employed to optimize culture conditions for the production of penicilazaphilone C, a new antineoplastic and azaphilone from the marine-derived fungus Penicillium sclerotiorum M-22 [ 150 ].…”
Section: High Throughput Methods To Streamline Cultivation Based Bmentioning
confidence: 99%
“…Table 4 shows the design and obtained experimental responses from PBD and the runs produced considerably improved results for kalafungin production. The effects of extraction parameters and production of antimicrobial metabolites from Micromonospora and relative yield was assessed by a three-level threefactor Box-Behnken design and reported [37]. Yang et al optimized the effective culture conditions of amoxicillin degrading bacteria using RSM [38].…”
Section: Media Optimization For Culture Conditions By Box-behnken Designmentioning
confidence: 99%
“…Carbon sources are essential components in the culture media. Several reports showed that the optimum antimicrobial agent production depends upon the type and concentration of carbon sources used in culture media such as (starch, glucose, maltose, fructose, glycerol, and molasses) (Amin et al, 2017a;Amin et al, 2017b;Pharm, 2010;Taurino et al, 2011;Wang et al, 2017;Abdelwahed et al, 2012). Also, the type and amount of nitrogen sources such as ammonium sulfate, ammonium nitrate, ammonium chloride, peptone, soya bean meal, and yeast extract greatly influence the antimicrobial production by Actinobacteria (Amin et al, 2017a;Amin et al, 2017b;Ahmad et al, 2017;Taurino et al, 2011;Wang et al, 2017;Abdelwahed et al, 2012).…”
Section: Factors Affecting Antibiotic Productionmentioning
confidence: 99%